SAVI Approach Paper 1: Core Values - SAVI (London, 2015)
Governance reform is about government and citizens working together in more responsive, inclusive and accountable ways for the benefit of ci tizens. More responsive, inclusive and accountable attitudes and behav iour on the part of government and non-government stakeholders are the critical factors which lead to meaningful reform processes, and repli cate and sustain reforms beyond the lifetime...